2017
DOI: 10.20452/pamw.4066
|View full text |Cite
|
Sign up to set email alerts
|

Using beta-lactam antibiotics in patients with a history of beta-lactam allergy: current concepts

Abstract: ABSTRACTβ-lactams are the most widely used antibiotic family, but they are also the most common cause of drug-induced hypersensitivity reactions. The estimated prevalence of reported penicillin allergy ranges between 9% and 12%, although a high percentage of patients with a history of penicillin allergy have no subsequent reactions on reexposure to β-lactams. A self-reported penicillin allergy has been associated with antimicrobial resistance, increased cost, intensive care admission, and death, making it esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…Articles included in the review (n = 23) adverse events. 18 Similarly, Moreno et al 19 emphasized the importance of allergy history in the diagnosis of b-lactam allergy. In contrast, other interventional studies indicated that patient-reported penicillin allergies can be unreliable and may result in needless changes in antibiotic therapy.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Articles included in the review (n = 23) adverse events. 18 Similarly, Moreno et al 19 emphasized the importance of allergy history in the diagnosis of b-lactam allergy. In contrast, other interventional studies indicated that patient-reported penicillin allergies can be unreliable and may result in needless changes in antibiotic therapy.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Thus, some researchers concluded that PST to confirm or rule out penicillin allergy should be a routine procedure. 19,23 If the allergy to penicillin is ruled out, patients can receive b-lactam antibiotics. 19,23,24 However, if the allergy to penicillin is confirmed, patients will be given non-b-lactam antimicrobials.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 3 more Smart Citations